Investigations of SiPM based large scintillation detectors. (November 2019) - Runtso, M F; Arkhangelskaja, I V; Arkhangelskiy, A I; Chasovikov, E N; Galper, A M; Egorov, A E; Leonov, A A; Naumov, P Yu; Naumov, P P; Suchkov, S I; Yurkin, Y T; Topchiev, N P
Abstract: Different types of light concentration for large fast scintillation detectors with silicon photomutipliers as photosensors for the satellite based gamma-ray telescope GAMMA- 400 are analysed. Some proposals for their possible implementations are made.